2019
DOI: 10.1016/j.conctc.2019.100462
|View full text |Cite
|
Sign up to set email alerts
|

Improving and sustaining the site investigator community: Recommendations from the Clinical Trials Transformation Initiative

Abstract: The Clinical Trials Transformation Initiative (CTTI) Strengthening the Investigator Community Project was prompted by the need to understand the reasons for high rates of turnover among investigators who lead US Food and Administration-regulated clinical trials at research sites. Because investigator knowledge and experience directly affect the quality and ultimate success of clinical trials, investigator turnover has important implications for the research enterprise, as well as the patients and other stakeho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Different barriers for investigators to participate in CTs have been identified as institutional support, infrastructure issues, staff support, administrative burden, time requirements, workload balance, data and safety reporting requirements, and dissatisfaction with finance-related issues ( 58 61 ). Accordingly, to these identified barriers, the Clinical Trials Transformation Initiative (CTTI) Strengthening the Investigator Community Project ( 62 ) has developed some recommendations focused on reinforcement of four critical categories of site-based research activity: developing site-based research infrastructure and staff, optimizing trial execution and conduct, improving site budget development and contract negotiations, and discovering opportunities for conducting additional trials ( 58 , 63 ).…”
Section: Principal Investigatormentioning
confidence: 99%
“…Different barriers for investigators to participate in CTs have been identified as institutional support, infrastructure issues, staff support, administrative burden, time requirements, workload balance, data and safety reporting requirements, and dissatisfaction with finance-related issues ( 58 61 ). Accordingly, to these identified barriers, the Clinical Trials Transformation Initiative (CTTI) Strengthening the Investigator Community Project ( 62 ) has developed some recommendations focused on reinforcement of four critical categories of site-based research activity: developing site-based research infrastructure and staff, optimizing trial execution and conduct, improving site budget development and contract negotiations, and discovering opportunities for conducting additional trials ( 58 , 63 ).…”
Section: Principal Investigatormentioning
confidence: 99%